Touch typing (Rugeley : Focus Multimedia Limited, 1990)
A totally interactive training system that guides the user through the art of touch typing. Includes an interactive game on key finger positions and sections on audio typing.
Ελάχιστες απαιτήσεις συστήματος: MPC 486 or above; Windows 95/98/ME or Windows NT/2000; 8 MB RAM; 3 MB hard drive space; 640x480x256 colours; 2x or faster CD-ROM speed; 16 bit soundblaster or 100% compatible.
Keywords: CD-ROMs.; Typewriting -- Interactive multimedia; Keyboarding -- Interactive multimedia